Knowledge, attitude and practice of married men on the contraceptive methods - Muda, Siti Mariam; Mohd. Said, Zeelawani (2016)
Family Planning is one of the main pillars of safe motherhood initiatives to reduce maternal morbidity and mortality. Effective contraceptive is important to spacing the number of childbirth and increase quality of life for mother and child. Objective of the Study To identify the knowledge, attitude and practice of men on contraceptive methods. Methodology A cross-sectional study was conducted among government staff working at Kuantan. Self-administer questionnaires were distributed to 113 male participants who purposely selected. SPSS version 20.0 was used to analyse the data involving a descriptive analysis, chi square and ANNOVA test. Results The prevalence rate of contraceptive used among married men was 60%. Approximately, 55% participants had lack of knowledge and 66% negative attitude on contraceptive. However, majority of participants know well on the use of condom compared to other methods. Factors influences the attitude of married men towards the use of contraceptive were due to religion, friends, family members, health services and culture. This study identified there is a statistically significant relationship between positive attitude and knowledge of married men toward contraceptive used (P= 0.04). Conclusion The knowledge and attitude of men towards contraceptive practice were still inadequate contribute to nearly half of the married man in this study did not use any method of contraceptive. Family planning programs should focus for both women and men. Nurse midwives at the hospital or health center need to educate more couples rather only women in giving advice about contraceptive.